2019
DOI: 10.3390/ijms20071601
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induction byHistone Deacetylase Inhibitors in Cancer Cells: Role of Ku70

Abstract: Histone deacetylases (HDACs) are a group of enzymes that regulate gene transcription by controlling deacetylation of histones and non-histone proteins. Overexpression of HDACs is found in some types of tumors and predicts poor prognosis. Five HDAC inhibitors are approved for the treatment of cutaneous T-cell lymphoma, peripheral T-cell lymphoma, and multiple myeloma. Treatment with HDAC inhibitors regulates gene expression with increased acetylated histones with unconfirmed connection with therapy. Apoptosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 137 publications
1
36
0
Order By: Relevance
“…Induction of apoptotic cell death represents one of the main mechanisms of anticancer effects promoted by HDAC inhibitors [ 57 , 58 , 59 , 60 , 61 ]. Regarding apoptosis signaling in cancer cells upon treatment with HDAC inhibitors, divergent effects have been demonstrated depending on the cellular context.…”
Section: Molecular Mechanisms Of Hdaci-promoted Anticancer Effectsmentioning
confidence: 99%
“…Induction of apoptotic cell death represents one of the main mechanisms of anticancer effects promoted by HDAC inhibitors [ 57 , 58 , 59 , 60 , 61 ]. Regarding apoptosis signaling in cancer cells upon treatment with HDAC inhibitors, divergent effects have been demonstrated depending on the cellular context.…”
Section: Molecular Mechanisms Of Hdaci-promoted Anticancer Effectsmentioning
confidence: 99%
“…More than 50 non-histone proteins, such as p53, Ku70, have been reported to be the substrates of HDACs. 46 So, we treated cells with trichostatin A (TSA), an inhibitor that is sensitive to Class I/II deacetylases, and then measured the impact of deacetylation inhibitor on DNA via Ku70-mediated IFN-k1 induction. The result indicated that treatment with TSA dosedependently increased IFN-k1 production (Figure 4E).…”
Section: Acetylation Regulates Ku70/dna-mediated Ifn-k1 Inductionmentioning
confidence: 99%
“…Notably, vorinostat has also been shown to induce necroptosis, a caspase-independent form of cell death [ 148 ]. Additionally, it was also suggested that HDACi cell death might be mediated by hyperacetylation of the NHEJ repair component Ku70 [ 149 , 150 , 151 ]. Ku70 acetylation and its interactions with Bax have been shown to be part of the apoptotic pathway, in a DNA repair-independent manner [ 152 ].…”
Section: Effects Of Hdac Inhibitors and Therapeutic Implications For Tumor Heterogeneitymentioning
confidence: 99%